Investigating the long and short-term effect of free ammonia and free nitrous acid levels on nitritation biomass of a sequencing batch reactor treating thermally pre-treated sludge reject water. (October 2022) - Statiris, E.; Dimopoulos, T.; Petalas, N.; Noutsopoulos, C.; Mamais, D.; Malamis, S.
Highlights: The long and short-term effect of FA/FNA on acclimated and non-acclimated biomass was investigated. For FA levels up to 90 mgL -1, no inhibition on AUR was observed. Acclimated biomass showed higher resilience on high FNA levels (KiFNA =7.4-18 μgL -1 ). KiFNA for non-acclimated biomass was between 2.2-9.9 μgL -1 . Non-competitive inhibition kinetics described well the FNA inhibition results. Abstract: This work examined the short and long-term effects of different free ammonia (FA) and free nitrous acid (FNA) levels on (i) acclimatized biomass treating sludge reject water via nitrite in a sequencing batch reactor (SBR) and (ii) non-aclimatized biomass treating municipal wastewater via nitrate in the activated sludge process. In the acclimatized biomass, the threshold for the transition from nitrification to nitritation was the FA increase to 10–20 mgNH3 -N/L while the SBR unit showed no inhibition on the ammonia uptake rate (AUR) at FA levels up to 65 mgNH3 -N/L. Short-term exposure of the acclimatized biomass on FNA showed that AUR inhibition could be more than 50 % for FNA concentration >10 μgHNO2 -N/L. The FNA inhibition results were simulated using non-competitive inhibition kinetics that showed that the inhibition constant corresponding to the FNA concentration that inhibits the process by 50 % (i.e. KiFNA ) was much higher in the acclimatized biomass.